A Method to Freeze Skin Samples for Cryobanks: A Test of Some Cryoprotectants for an Endangered Deer - Campos Cassavia Cintra de Oliveira, Laura [UNESP]; Queiroz Vacari, Gabrielle [UNESP]; Maurício Barbanti Duarte, José [UNESP] (SAGE Publications, 2024)
The genetic diversity of endangered deer species, such as Mazama jucunda, can be preserved with the help of somatic cell cryopreservation. This procedure allows obtaining several cells from the individual even after its death, which is very important for applications in reproductive biotechnologies. This study's objective was to test cryopreservation protocols of skin fragments of M. jucunda, using different cryoprotectants in slow freezing. We evaluated four treatments, composed of three cryoprotectants, dimethyl sulfoxide (DMSO), polyvinylpyrrolidone (PVP), and ethylene glycol (EG), used alone and in combination. There was also a control group where the tissue did not undergo cryopreservation. Skin fragments were collected from the medial region of the pelvic limbs of three individuals. Each fragment was divided into 10 equal parts, standardized by weight, making two pieces for each treatment and control from each animal. The collected fragments were evaluated in culture, based on the speed of occupation of the free spaces of the cell culture flask. Cell viability was also evaluated using Trypan Blue dye and the mitotic index to understand the effect of toxicity and freezing on cell membrane integrity and cell division capacity, respectively. The treatments that used association with PVP proved to be more damaging to the cells, taking longer to reach confluence. EG alone showed better results than DMSO in the slow-freezing protocol. Clinical Trial Registration Number is 1390/21.
Keywords: biobank; cell culture; deer; endangered species; somatic cells cryopreservation